DICER1 Syndrome and Cancer Predisposition: From a Rare Pediatric Tumor to Lifetime Risk - Caroleo, Anna Maria; De Ioris, Maria Antonietta; Boccuto, Luigi; Alessi, Iside; Del Baldo, Giada; Cacchione, Antonella; Agolini, Emanuele; Rinelli, Martina; Serra, Annalisa; Carai, Andrea; Mastronuzzi, Angela (Frontiers in Oncology, 2021)
DICER1 syndrome is a rare genetic condition predisposing to hereditary cancer and caused by variants in the DICER1 gene. The risk to present a neoplasm before the age of 10 years is 5.3% and 31.5% before the age of 60. DICER1 variants have been associated with a syndrome involving familial pleuropulmonary blastoma (PPB), a rare malignant lung tumor, primarily affecting children before the age of 6 years and representing the most common life-threatening manifestation of DICER1 syndrome (Messinger et al. 2015). Type I, II, III and Ir (type I regressed) PPB are reported with a 5-year overall survival ranging from 53% to 100% (for type Ir). DICER1 gene should be screened in all patients with PPB and considered in others tumors mainly in thyroid gland neoplasia (multinodular goiter, adenomas, and/or thyroid cancer), ovarian tumors (Sertoli-Leydig cell tumor, gynandroblastoma, and sarcoma), and cystic nephroma. A prompt identification of this syndrome is necessary to plan a correct follow-up and screening during lifetime.